STRATEGI KOMUNIKASI PADA MASYARAKAT MULTIKULTURAL - Rini Fitria (Institut Agama Islam Negeri Bengkulu, 2017)
Multicultural society is a multi-cultural, religious, ethnic and racial society.Communication process is done requires a certain strategy so that interactionbetween individuals in the community can take place properly. The communicationstrategy is carried out by elements of the society, from traditional leaders, ethnicleaders, religious leaders, community leaders to even the smallest element of society. The communication strategy should be able to demonstrate its operational ways practically, in the sense that the approach may vary from time to time depending on circumstances.